Typology of Nightclubs in São Paulo, Brazil: Alcohol and Illegal Drug Consumption, Sexual Behavior and Violence in the Venues. (19th September 2018) - Carlini, Claudia M.; Sanchez, Zila M.
ABSTRACT: Background : Nightclubs are venues in which excessive alcohol use and illegal drug consumption occur in addition to other high-risk behaviors, such as violence and sexual risk behaviors. Environmental factors common in nightclubs and the personal characteristics of patrons might increase the risk of these events. To better understand the relationship between these factors, typologies were formulated that clustered nightclubs according to definite profiles to identify differences to be taken into consideration in preventive interventions. Objectives : The present study aim was to construct a typology of nightclubs in São Paulo, Brazil. Methods : This typology was constructed using mixed methods research through the triangulation of several data sources as follows: 307 hours of ethnographic observation at 31 nightclubs, 8 focus group sessions with nightclub patrons (n = 34) and 30 semi-structured interviews with nightclub employees. Content analysis and qualitative typology were used. Results : Four nightclub types were defined based on four analyzed thematic axes (Intoxicating, Violent, Dancing and Highly Sexualized nightclubs). Excessive alcohol use was detected in almost all of the investigated nightclubs, and drug use was observed in approximately one-third of them. Triangulation of the data revealed a relationship among environmental factors (especially alcohol sales strategies and promotion and the availability of areas for sex) and a more considerable presence of high-risk behaviors. Conclusions : The study shows that nightclubs are settings in which high-risk behaviors are potentiated by facilitating environmental factors as well as by the lack of laws restricting excessive alcohol use stimulated by the promotion strategies applied at these venues.